(untitled) (Bangladesh Heart Journal, 2024)
Introduction: Coronary artery disease is one of the leading causes of non-communicable diseases related deaths worldwide. Decreased serum high-density lipoprotein level are associated with an increased severity of coronary artery disease. Present study aims to evaluate the association between this low HDL level and the severity of coronary artery disease assessed by SYNTAX Score in patients with non-ST elevation Myocardial infarction. Materials & Methods: This was a cross sectional study conducted in the Department of Cardiology at National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh, from May 2020 to April 2021, on 170 admitted adult patients of non-ST elevated myocardial infarction undergoing coronary angiogram. Study population was divided in two groups; Group-I: Respondents with HDL level ≥ 40 mg/dl, Group-II: Respondents with HDL level < 40 mg/dl. Transthoracic echocardiography was done before coronary angiography. All coronary lesions with diameter stenosis > 50% in vessels > 1.5 mm was scored, using the SYNTAX algorithm. A low score was defined as ≤ 22, an intermediate score as 23 to 32, and a high score as ≥ 33. To determine statistical significance, Chi-square test and independent sample t-test were considered according to applicability. P value of < 0.05 was considered statistically significant. Results: Highest proportion of respondents were from age group 51 – 60 years, 48.2% and 43.5% for group-I and group-II respectively. Study population was male predominant, 88.2% among patients from group-I and 83.5% among patients from group-II. Smoking was the most prevalent risk factor for group-I patients at 58.8%. Hypertension was the most prevalent risk factor for group-II patients at 45.9%. Mean total cholesterol, low-density lipoprotein and high-density lipoprotein were higher among patients from group-I than group-II and these differences were statistically significant (p < 0.05). Mean triglycerides was higher among patients from group-II than group-I and this difference was statistically significant (p < 0.05). Triple vessel was more prevalent (36.5% vs 22.4%) among patients from group-II than group-I and this difference was statistically significant (p < 0.05). Mean SYNTAX score (SS) was higher among patients from group-II than group-I, 17.4 ± 8.6 and 11.5 ± 8.4 respectively, and this difference was statistically significant (p < 0.05). There was strong negative correlation between HDL level and Syntax score (r = - 0.299, p < 0.05). Conclusion: Present study demonstrated significant negative correlation between low serum HDL levels with severity of coronary artery disease among patients with non-ST elevated myocardial infarction. Serum HDL levels can be used as a predictor for the severity of coronary artery disease among such patients. Bangladesh Heart Journal 2024; 39(2): 138-143